Strategi Guru dalam Menginternalisasi Nilai Pancasila di Madrasah Ibtidaiyah: Studi Kasus Pembelajaran PKn di MI Pekanbaru - Zulhidah; Nabiha; Fatimah Azzahra; Nurul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstract The moral decline among Indonesian students necessitates early character education, particularly within Madrasah Ibtidaiyah (MI), which offers a strategic Islamic educational ecosystem. This study aims to analyze the strategies, challenges, and innovative solutions employed by Civic Education teachers in internalizing Pancasila values at the elementary madrasah level. Employing a qualitative descriptive approach with a single-case study design, data were collected through semi-structured interviews and classroom observations at an MI A in Pekanbaru, and analyzed using the Miles and Huberman model (data reduction, display, and verification). The findings reveal that Pancasila values were effectively internalized through contextual methods (roleplay, rhythmic songs, and real-life examples) and digital video media, which proved superior to physical posters. The integration of the First Principle with Islamic routines (Tahfidz and Dhuha prayer) naturally fostered a religio-nationalist character. Key challenges included limited reading literacy among lower-grade students and psychosocial-domestic influences, which were mitigated through teachers’ affective sensitivity, WhatsApp-based parent collaboration, and personalized interventions. Consequently, this study recommends the implementation of the "Hybrid Spirit" pedagogical model, which integrates kinesthetic, audiovisual, and emotional stabilization activities, alongside institutional efforts to elevate the status of Civic Education to parity with religious subjects in MI curricula.